Learning Basketball Dribbling Techniques in High School: Integrated Problem Based Learning Model with Audiovisual Media - Putra, M. Ilham Nur; Hudain, Muh. Adnan; Wahyudin, Wahyudin; Fahrizal, Fahrizal; Hasyim, Hasyim (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
The objective of this study was to determine if a problem-based learning model integrated with audiovisual media can improve the learning outcomes of basketball dribbling techniques in public high school students. This type of research is classroom action research, which is carried out during two learning cycles consisting of four stages: planning, implementation of action, observation, and reflection. The sample in this study was 36 students in class X.I of public high school 16 Makassar. The study employed the purposive sampling technique. The instrument used in this study was a test of basketball dribbling technique ability. The data analysis technique used quantitatively is descriptive methods by finding the average and relative frequency percentage and qualitatively using observation methods. The results of the study showed that in the pre-cycle, 8 students completed it with a percentage of 22%, and 28 students did not complete it with a percentage of 78%. In Cycle I, students who completed the study increased to 27 students with a percentage of 75%, and 9 students did not complete the study with a percentage of 25%. In Cycle II, there was a significant increase in learning outcomes, namely students who completed became 36 students with a percentage of 100% and did not complete 0 students with a percentage of 0%. In conclusion, using a problem-based learning model with audiovisual media can help improve basketball dribbling skills for students at public high schools.